(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Training of speech culture of pupils and students in the native language in the system of secondary and higher education is one of actual problems. In this regard various works are carried out. With the purpose to improve the use of words and to form language and communicative competence of pupils, in accordance with the decision of the RK Ministry of Education and Science, additional subjects such as «Program of the in-depth training of the Kazakh language», «Speech culture», «Speech culture and rhetoric» were introduced. The role of expressive language means takes a special place in the development of the language of pupils. In this article the scientific-theoretical characteristics, the research in the Russian and Kazakh linguistics, definitions of expressive language means are considered.